Difficulties in selecting an appropriate neonatal thyroid stimulating hormone (TSH) screening threshold. Issue 3 (12th August 2009) - Korada, Srinivasa Murthy; Pearce, Mark; Ward Platt, Martin P; Avis, Enid; Turner, Steve; Wastell, Hilary; Cheetham, Tim
Abstract : Background: The UK Newborn Screening Programme Centre recommends that a blood spot thyroid stimulating hormone (TSH) cut-off of 10 mU/l is used to detect congenital hypothyroidism (CHT). As the value used varies from 5 to 10 mU/l, we examined the implications of altering this threshold. Methods: Our regional blood spot TSH cut-off is 6 mU/l. Positive or suspected cases were defined as a TSH >6 mU/l throughout the study period (1 April 2005 to 1 March 2007). All term infants (>35 weeks) whose first TSH was 6–20 mU/l had a second TSH measured. The biochemical details of infants with a TSH between 6.1 and 10.0 mU/l and then >6 mU/l on second sampling were sent to paediatric endocrinologists to determine approaches to management. Results: 148 of 65 446 infants (0.23%) had a first blood spot TSH >6.0 mU/l. 120 were term infants with 67 of these (0.1% of all infants tested) having a TSH between 6.1 and 10.0 mU/l and 53 a TSH >10.0 mU/l. Of the 67 term infants with a TSH between 6.1 and 10.0 mU/l on initial testing, four continued to have a TSH >6 mU/l. One with a TSH >10 mU/l and one infant with a TSH <10 mU/l on the second blood spot have been diagnosed with CHT. The survey of endocrinologists highlighted significant differences in practice. Conclusions: A reduced threshold of 6 mU/l will increase the number of false positive term infants by 126%, but abnormalities of thyroid function requiring treatment will be detected. We suspect that the additional expense involved in setting a lower threshold is justified.